Thursday
March 23, 2017

Post a New Question

Posted by on Saturday, January 24, 2009 at 5:49pm.

log_3(2x - 1) = 2, Find x.

Here's what I've done:

log_3(2x) * log_3(1) = 2

log2x/log3 * log1/log3 = 2

trial and error...

log2 (2*1.4)/log3 * 0 = 2.03...

x = 1.4

I think I did it wrong because anything that multiplies with 0 gives you 0...

  • Math - logs - , Saturday, January 24, 2009 at 5:55pm

    3^log_3(2x - 1) = 3^2
    but 3^log3 a = a for any a
    so
    2 x - 1 = 3^2 = 9
    2 x = 10
    x = 5

  • Math - logs - , Saturday, January 24, 2009 at 5:59pm

    thank you! so if I get a problem like that, all I do is raise the base to the power of the log?

  • Math - logs - , Saturday, January 24, 2009 at 6:13pm

    yep

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question